PENDIDIKAN KELUARGA SEBAGAI PONDASI AWAL KARAKTER BANGSA - IG AGUNG JAYA SURYAWAN (Purwadita : Jurnal Agama dan Budaya, 2018)
The relationship that exists between parents and children should be based on the principle of mutual respect and compassion. If parents always prioritize a personal approach with the outpouring of affection, then will form a great confidence in the child. The child will be open to his / her parents so that any problems can be searched for the key of the settlement. In addition, parents are more likely to give direction and counsel and to abandon coercion and intimidation. The child's behavior will gradually form towards a good personality. A strong push constantly is expected from parents. The figure of a democratic parent does not prioritize his personal interests, but still appreciates and cares for the child's interests as an individual among the human community. In other words, parents always see the common interest as a barrier to the freedom of this person. The background of parenting found by a child is certainly very influential on further developments, because the things that he finds from the parenting pattern of his parents will be a provision of his attitude and behavior in his life someday. The family has a very important role in developing the child's personal. The loving care of parents and education about the religious and socio-cultural values it provides is a conducive factor for preparing children to be private and healthy members of society that reflect the character of the Nation.